Antagonistic Coevolution Limits the Range of Host Defense in C. elegans Populations - Lewis, Jordan A.; Penley, McKenna J.; Sylla, Hannan; Ahumada, Sebastián Durán; Morran, Levi T. (Frontiers in Cellular and Infection Microbiology, 2022)
Host populations often evolve defenses against parasites due to the significant fitness costs imposed by infection. However, adaptation to a specific parasite may alter the effectiveness of the host’s defenses in general. Consequently, the specificity of host defense may be influenced by a host population’s evolutionary history with parasites. Further, the degree of reciprocal change within an interaction may profoundly alter the range of host defense, given that antagonistic coevolutionary interactions are predicted to favor defense against specific parasite genotypes. Here, we examined the effect of host evolutionary history on host defense range by assessing the mortality rates of Caenorhabditis elegans host populations exposed to an array of Serratia marcescens bacterial parasite strains. Importantly, each of the host populations were derived from the same genetic background but have different experimental evolution histories with parasites. Each of these histories (exposure to either heat-killed, fixed genotype, or coevolving parasites) carries a different level of evolutionary reciprocity. Overall, we observed an effect of host evolutionary history in that previously coevolved host populations were generally the most susceptible to novel parasite strains. This data demonstrates that host evolutionary history can have a significant impact on host defense, and that host-parasite coevolution can increase host susceptibility to novel parasites.